GESTIÓN FINANCIERA, ADMINISTRATIVA, TRIBUTARIA, AUDITORÍA Y CONTROL - MORAN CHILUIZA GABRIELA NORALISA (2024)
The objective was to determine how the scheduling of medical care impacts the health service in the peasant social security - Los Ríos. The descriptive explanatory type of research, the analytical, synthetic, inductive and deductive methods were used and the quantitative approach was used. The study population was all the affiliates of the peasant insurance of the IESS Los Ríos, who were 5840 during 2022 and a sample of 124 affiliates was determined. The results showed characteristics related to the scheduling of the appointment which is greatly affected by connectivity problems and means of transportation, the orientation to schedule an appointment often generates confusion in users and the timeliness of the scheduling that is often not achieved, since appointments are given for dates very far from the need for care. Points were identified regarding universal service that show little quality care in health services, in terms of evaluation, primary care is necessary as well as referrals and counter-referrals and in terms of resolution, it requires infrastructure and equipment and above all, trained health personnel. It is concluded that the relationship between the variables Medical Care Scheduling and Health Service is significantly positive, the correlation obtained was Rho = 0.893, which establishes a high relationship between the variables and that the timely scheduling of medical care in the insured of the peasant social security explains 79.74% of the pertinent health service that said insured receive.